A4.2 Chronic kidney disease associates with worse trabecular mechanical performance in hip osteoarthritis patients independently of bone mineral density. (31st January 2014) - Sepriano, A; Gonçalves, M J; Rodrigues, A; Lopes, A; Caetano-Lopes, J; Fonseca, J E; Canhão, H
Abstract : Background: Previous studies have shown that high Bone Mineral Density (BMD) in patients with advanced hip osteoarthritis was not a protective factor for bone fragility. Although measures of bone mineral content are strongly correlated with bone mechanical performance, they do not fully explain the response of bone to mechanical stresses. Bone abnormalities are found in patients with Chronic Kidney Disease (CKD). Evaluating the effect of CKD on bone mechanical properties in patients with hip OA may shed some light into the complex pathways of joint pathology in these patients. Objective: To assess the association between CKD and trabecular bone mechanical properties in patients with hip osteoarthritis. Materials and Methods: 37 Hip OA patients submitted to total hip replacement surgery were recruited. Clinical and demographical data were collected, a dual X-ray absorptiometry (DXA) was performed and fasting blood samples were collected at the time of surgery to assess creatinine and parathormone (PTH) serum levels. Previous creatinine levels were assessed to establish chronicity. Femoral epiphyses were collected and trabecular bone cylinders drilled in order to perform compression mechanical tests. Results: Among the 37 hip OA patients 8 (21.6%) had CKD and 29 (78.4%) had normal renal function. There were no differences between groups regarding gender, age, body mass index and T-score (-1.5 vs -2.1, p = 0.305). However, there were more smokers among patients with CKD as compared to those with normal renal function (50% vs 10.3%, p = 0.027). As expected, patients with CKD had higher PTH levels as compared to those with normal renal function, however not reaching statistical significance (100.05 pgmL vs 37.41 pg/mL, p = 0.71). The association between trabecular bone mechanical properties with CKD tested by univariable analysis in hip OA patients revealed to be statistical significant only for stiffness (β = -187.19; p = 0.045). Multivariate regression analysis using forward selection demonstrated that in hip OA patients CKD was negatively associated with strength (β = -12.02; p = 0.038), stiffness (β = -471.77; p = 0.043) but not with toughness (β = -0.03; p = 0.192) adjusting for age, gender, BMI, smoking status, and T-score. The inclusion of PTH serum levels on each model renders the association between CKD and trabecular bone mechanical properties not statistical significant. Conclusions: Our work suggest that, in patients with advanced hip OA, CKD is an independent risk factor for poor trabecular bone mechanical properties and that this effect is independent of bone mineralization status.